A paired training curriculum and internal monitoring program for clinical research regulatory compliance in the emerging era of the single Institutional Review Board. Issue 4 (9th October 2017) - Jarrell, T. Che; Hamblin, Frances; Ford, Daniel E.; Powell, Sylvia R.; Ellen, Jonathan M.; Goldenberg, Neil A.
Abstract : Background: Academic health systems and their investigators are challenged to systematically assure clinical research regulatory compliance. This challenge is heightened in the emerging era of centralized single Institutional Review Boards for multicenter studies, which rely on monitoring programs at each participating site. Objective: To describe the development, implementation, and outcome measurement of an institution-wide paired training curriculum and internal monitoring program for clinical research regulatory compliance. Methods: Standard operating procedures (SOPs) were developed to facilitate investigator and research professional adherence to institutional policies, federal guidelines, and international standards. An SOP training curriculum was developed and implemented institution-wide. An internal monitoring program was launched, utilizing risk-based monitoring plans of pre-specified frequency and intensity, assessed upon Institutional Review Boards approval of each prospective study. Monitoring plans were executed according to an additional SOP on internal monitoring, with monitoring findings captured in a REDCap database. Results: We observed few major violations across 3 key domains of clinical research conduct and demonstrated a meaningful decrease in the rates of nonmajor violations in each, over the course of 2 years. Conclusion: The paired training curriculum and monitoring program is a successful institution-wide clinical research regulatory compliance model that will continue to be refined.